The effects of exercise on the immune parameters and stress hormones in elite sportswomen - Karacabey, K.; Saygın, Ö.; Ozmerdivenli, R.; Zorba, E.; Gödekmerdan, A. (My University, 2004)
This study was conducted with the aim of determining the differences in the humoral immune parameters, serum ACTH and cortisol levels existing between elite sportswomen and those leading sedentary lives and the effect of acute aerobic and anaerobic exercise on these parameters. In this study, 40 sportswomen (Groups 1 and 2) and 20 women leading sedentary lives (Group 3) were enrolled. Twenty of the 40 sportswomen (Group 1) were made to exercise aerobically on a treadmill for 30 minutes while the other 20 women (Group 2) were subjected to the Wingate effort test for 30 minutes. Before exercising (at 8.30 a.m), at the end of the exercise, and 4 hours after exercising and on days 2 and 5 after exercising, a total of 5 blood samples each approximately 5ml were drawn from each subject. The IgA, IgG, IgM, C3 and C4 determinations were done turbidometrically. Before exercise: the mean IgA, and IgG values in the sporting groups, and the mean cortisol levels in the sedentary group were found to be significantly higher statistically (p<0.05). After Exercise: Whereas the C3 and C4 levels decreased significantly at the end of the exercsie in Group 1 (p<0.05), the IgA, IgG (p<0.05) and IgM levels (p<0.01) at the 4th and 5th determinations were observed to be significantly higher. The cortisol and ACTH levels were found to have increased significantly (p<0.05). In Group 2, no changes were observed in the IgA, IgG and IgM levels. The C3 and C4 levels however, were found to have fallen in the samples taken inmmediately following the exercise (p<0.05). In conclusion, whereas the anaerobic exercise of short duration did not lead to an increase in the cortisol and ACTH levels in the sporting women, aerobic exercise was observed to have led to changes in the parameters of the immune system by increasing the cortisol and ACTH hormone levels depending on the duration and intensity of the exercise. According the data obtained from the study we conclude that regular and moderate exercise have favorable effects on the immune system. © 2004 Taylor and Francis Group, LLC.